Transcriptome Analysis of Ophraella communa Male Reproductive Tract in Indirect Response to Elevated CO2 and Heat Wave - Gao, Xuyuan; Tian, Zhenya; Zhang, Yan; Chen, Guangmei; Ma, Chao; Tian, Zhenqi; Cui, Shaowei; Lu, Yongyue; Zhou, Zhongshi (Frontiers in Physiology, 2020)
Increase in atmospheric CO2 directly affects the insect physiology and behaviour, and indirectly affects the herbivorous insects by affecting their hosts. The increase in atmospheric CO2 is accompanied by an increase in temperature and heat waves. Ophraella communa LeSage is a natural enemy of Ambrosia artemisiifolia (common ragweed).The development and reproduction of this beetle is weakened upon eating common ragweed grown under stress conditions. As female behaviour and physiology alter after mating, the reproductive tract of males is likely to modulate reproduction and development in this species. Herein, the transcriptional profiles of testes and accessory glands from male O. communa individuals feeding on common ragweed under conditions of high CO2concentration and heat waves and that grown under ambient CO2concentration were compared. Differentially expressed genes (DEGs) were identified between the same tissues from beetles fed on common ragweed grown under different stress conditions. There were 3, 2, 3, 1and 5 genes related to decomposition and transport of macromolecular substances, host location, stress response, reproduction, and poisonous food-utilization. No expected response was observed in the male reproductive tract, but some of the identified DEGs might control the development of the population. The results presented here should be helpful in guiding future studies on deciphering the indirect response of other organs to high CO2 concentration and heat waves, as well as the functions of seminal fluid proteins in O. communa.